High-stability composite lithium metal negative electrode material, preparation method thereof and battery
By growing a copper oxide coating layer in situ on the surface of a copper foil current collector and constructing an artificial SEI layer, the problems of dendrite growth and volume change in lithium metal anodes were solved, thereby improving the electrochemical performance and safety of the battery.
Patent Information
- Application Number
- CN202511267139.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-05
- Publication Date
- 2025-12-05
AI Technical Summary
Lithium metal anodes suffer from dendrite growth, severe side reactions, and large volume changes, leading to capacity decay and safety hazards.
A lithium-loving copper oxide coating layer is grown in situ on the surface of a copper foil current collector. A high-performance lithium metal layer is constructed through an electroplating process. An artificial SEI layer is then built on this structure to form a sandwich-structured lithium metal composite anode.
It improves dendrite growth, reduces side reactions between lithium metal and electrolyte, alleviates volume expansion, enhances battery electrochemical performance, especially rate performance and cycle life, improves capacity decay, and enhances safety.
Smart Images

Figure CN121060792A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of batteries, in particular to a high-stability composite lithium metal negative electrode material, a preparation method thereof and a battery. BACKGROUND
[0002] The lithium metal negative electrode is considered to be the most ideal negative electrode material for high-energy-density batteries because it has an ultra-high theoretical specific capacity (3860 mAh / g) and an extremely low oxidation-reduction potential (-3.04 V vs. H + / H2).
[0003] However, the lithium metal negative electrode provided by the related art has the problems of dendrite growth, serious side reactions, large volume change, and thus capacity attenuation and safety hazards. SUMMARY
[0004] The present application aims to provide a high-stability composite lithium metal negative electrode material, a preparation method thereof and a battery. The negative electrode material prepared by the preparation method can be used to prepare a battery. The preparation method grows a lithiumophilic copper oxide coating layer in situ on the surface of a copper foil current collector, constructs a high-performance lithium metal layer through an electroplating process, and constructs an artificial SEI layer on the basis of the structure to finally form a sandwich-structure lithium metal composite negative electrode. This can improve the problem of dendrite growth, reduce the side reactions between the metal lithium and the electrolyte, relieve the volume expansion, improve the electrochemical performance of the battery, especially the rate capability and the cycle life, improve the capacity attenuation problem, and improve the safety.
[0005] The present application is implemented as follows: In a first aspect, the present application provides a preparation method of a high-stability composite lithium metal negative electrode material, comprising: immersing a copper foil into a soaking solution, and performing a hydrothermal reaction to obtain a three-dimensional copper foil with a three-dimensional copper oxide structure; immersing the three-dimensional copper foil in an electroplating solution to perform electroplating to deposit an electroplated lithium layer on the surface of the three-dimensional copper foil, and obtain a pre-prepared negative electrode material; immersing the pre-prepared negative electrode material in an artificial SEI infiltration solution to form an SEI protective layer on the surface of the electroplated lithium layer.
[0006] In an optional embodiment, the temperature of the hydrothermal reaction is 60-90°C.
[0007] In an optional embodiment, the current density of the electroplating is 1-50 mA / cm 2 ; and / or, the capacity of the electroplating is 0.1-10 mAh / cm 2 ; and / or, the time of the electroplating is 1-45 min.
[0008] In an optional embodiment, the current density of the electroplating is 10-40 mA / cm 2 ; and / or, The capacity of the electroplating is 1-3 mAh / cm 2 ; and / or, The time of the electroplating is 3-15 min.
[0009] In an optional embodiment, the pre-prepared negative electrode material is infiltrated with the artificial SEI infiltrating solution at a temperature of 10-80℃; and / or, The time of infiltrating the pre-prepared negative electrode material with the artificial SEI infiltrating solution is 1-600s.
[0010] In an optional embodiment, the soaking solution comprises a strong alkali, a halogenated metal salt, a persulfate salt, and a sulfate salt; wherein, The strong alkali comprises at least one of sodium hydroxide, potassium hydroxide, magnesium hydroxide, calcium hydroxide, etc.; The halogenated metal salt comprises at least one of sodium chloride, potassium chloride, magnesium chloride, calcium chloride, zinc chloride, iron chloride, copper chloride, etc.; The persulfate salt comprises at least one of sodium persulfate, potassium persulfate, etc.; The sulfate salt comprises at least one of sodium sulfate, potassium sulfate, magnesium sulfate, zinc sulfate, iron sulfate, and copper sulfate.
[0011] In an optional embodiment, the preparation method of the soaking solution comprises dissolving 10-200 mM of the strong alkali, 10-100 mM of the halogenated metal salt, 1-20 mM of the persulfate salt, and 0.01-1.0 mM of the sulfate salt in 100 mL of water, stirring uniformly, and heating to 60-90℃.
[0012] In an optional embodiment, the electroplating solution comprises a lithium salt, a solvent, and an additive; wherein, The lithium salt comprises at least one of LiTFSI, LiPF6, Li2S6, LiNO3, LiFSI, and the concentration of any one of LiTFSI, LiPF6, Li2S6, LiNO3, LiFSI is 0.2-2.0 mol / L; The solvent comprises at least one of DME, DOL, DMC, EC, PC, EMC, DUGLYME, FEC, MTFA, and MP; The additive includes but is not limited to nitrate and the like, for example: one or more of lithium nitrate (LiNO3), lithium nitrite (LiNO2), potassium nitrate (KNO3), cesium nitrate (CsNO3), magnesium nitrate (Mg(NO3)2), barium nitrate (Ba(NO3)2), potassium nitrite (KNO2) and cesium nitrite (CsNO2), wherein the mass percentage concentration of any one of LiNO3, LiNO2, KNO3, CsNO3, Mg(NO3)2, Ba(NO3)2, KNO2 and CsNO2 is 0.5-3.0%.
[0013] In an optional embodiment, the artificial SEI infiltrate includes a metal salt and an organic solvent; wherein, The metal salt includes 5.0-200.0 mmol / L silver trifluoromethyl sulfonate and the like; The organic solvent includes at least one of N-methyl pyrrolidone, dimethyl sulfoxide, tetrahydrofuran, ethylene glycol dimethyl ether and N,N-dimethylformamide.
[0014] In a second aspect, the present application provides a high-stability composite lithium metal negative electrode material prepared by the preparation method of the high-stability composite lithium metal negative electrode material according to any one of the preceding embodiments.
[0015] In a third aspect, the present application provides a battery, wherein the negative electrode of the battery is prepared from the high-stability composite lithium metal negative electrode material according to the preceding embodiments.
[0016] The present application has the following beneficial effects: The preparation method of the high-stability composite lithium metal negative electrode material provided by the embodiments of the present application first forms a dense copper oxide three-dimensional surface on the surface of a copper foil through a hydrothermal reaction, and the micron-level interconnected porous structure and high surface area of the self-grown nanosheet copper oxide three-dimensional structure can reduce the nucleation resistance of lithium, increase the nucleation sites, and reduce the polarization voltage, so that the ion and electron migration is less limited, ensuring uniform lithium nucleation and continuous smooth lithium plating in the subsequent process, and comprehensively improving the electrochemical stability of the composite lithium metal negative electrode, that is, by constructing a three-dimensional porous copper current collector, not only can the local current density be reduced and the growth of lithium dendrites be inhibited, but also the deposited lithium can be accommodated to relieve the volume change. In addition, as a lithiumophilic material, the lithiumophilic surface of the copper oxide material can contribute part of the capacity during the cycling process and exhibit excellent cycling stability in the subsequent cycling process.
[0017] After electroplating metal lithium on the three-dimensional copper foil, an SEI protective layer is generated on the surface of the electroplated lithium layer by infiltration, which not only can meet the long-term storage of the negative electrode material in an oxygen-containing environment, reduce the preparation cost caused by the production environment demand, but also can optimize the ion transmission path, reduce the generation of lithium dendrites, and improve the electrochemical performance, especially the rate performance and cycle life.
[0018] The high-stability composite lithium metal negative electrode material provided by the embodiment of the present application can improve the problem of dendrite growth, reduce the side reaction between metal lithium and electrolyte, relieve volume expansion, improve the electrochemical performance of the battery, especially the rate performance and cycle life, and improve the capacity fading problem.
[0019] The battery provided by the embodiment of the present application can improve the electrochemical performance of the battery, especially the rate performance and cycle life, and improve the capacity fading problem. Moreover, the negative electrode material used by the battery of the present application is the high-stability composite lithium metal negative electrode material prepared by the preparation method described above. Compared with pure lithium metal negative electrode, the battery adopts the process of electroplating lithium, and can use less and thinner lithium metal, which is conducive to improving the utilization rate of lithium metal and reducing the cost. At the same time, the artificial SEI protective layer of the high-stability composite lithium metal negative electrode material can make the lithium metal exist stably in the air atmosphere for at least 2 hours, which can effectively improve the intrinsic safety of the battery cell body and the cell manufacturing process. BRIEF DESCRIPTION OF DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following will briefly introduce the drawings needed to be used in the embodiments. It should be understood that the following drawings only show some embodiments of the present application, and therefore should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can also be obtained without creative labor on the basis of these drawings.
[0021] Figure 1 It is a scanning diagram of the three-dimensional copper foil with a three-dimensional copper oxide structure in the test example 1 of the present application under a high-power electron microscope; Figure 2 It is a scanning diagram of the three-dimensional copper foil with a three-dimensional copper oxide structure in the test example 1 of the present application under a low-power electron microscope; Figure 3 It is a half-cell cycle performance diagram of the test example 1 and the test example 2 of the present application; Figure 4 It is a half-cell cycle curve diagram of the test example 1 of the present application; Figure 5 It is a half-cell cycle curve diagram of the test example 2 of the present application; Figure 6 It is a scanning diagram of the three-dimensional copper foil with a three-dimensional copper oxide structure in the test example 3 of the present application under a high-power electron microscope; Figure 7 It is a scanning diagram of the three-dimensional copper foil with a three-dimensional copper oxide structure in the test example 3 of the present application under a low-power electron microscope; Figure 8 It is a scanning diagram of the three-dimensional copper foil with a three-dimensional copper oxide structure in the test example 4 of the present application under a high-power electron microscope; Figure 9 Scanning electron microscope (SEM) image of the three-dimensional copper foil with copper oxide three-dimensional structure in Test Example 4 of the present application; Figure 10 LFP full battery rate cycle curve of Test Example 5, Test Example 6 and Test Example 7 of the present application; Figure 11 NCM full battery rate cycle curve of Test Example 5, Test Example 6 and Test Example 7 of the present application; Figure 12 LFP full battery 1C rate cycle curve of Test Example 5, Test Example 8 and Test Example 9 of the present application; Figure 13 LFP full battery rate cycle curve of Test Example 10 and Test Example 11 of the present application; Figure 14 LFP full battery 1C rate cycle curve of Test Example 10 and Test Example 11 of the present application; Figure 15 XRD test result graph of Test Example 12 of the present application; Figure 16 Exposure test result graph of Test Example 13; Figure 17 In-situ XRD test result graph of Test Example 14; Figure 18 Detection result graph of Test Example 15. DETAILED DESCRIPTION
[0022] In order to make the objects, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described clearly and completely below. If specific conditions are not specified in the embodiments, conventional conditions or manufacturer recommended conditions are used. If the reagents or instruments used are not specified by the manufacturer, they are all conventional products that can be purchased on the market.
[0023] Lithium metal negative electrode is a preferred material for preparing batteries.
[0024] However, the inventors have found that due to the high reactivity of lithium metal, lithium metal can react with almost all electrolyte components, and a solid electrolyte interface (SEI) film is rapidly formed on the surface of lithium metal. Unlike graphite negative electrodes, the SEI film formed by lithium metal negative electrodes is very fragile and extremely uneven, which easily leads to the formation of uneven lithium ion flux under the electrolyte film and triggers the local nucleation and growth of lithium dendrites, thereby causing capacity decay and safety hazards.
[0025] To improve the above problems, the present disclosure provides a new preparation method of a high-stability composite lithium metal negative electrode material. The negative electrode material prepared by the preparation method can be used to prepare a battery. The preparation method grows a lithiumophilic copper oxide coating layer in situ on the surface of a copper foil current collector, constructs a high-performance lithium metal layer through an electroplating process, and constructs an artificial SEI layer on the basis of the structure to finally form a sandwich structure lithium metal composite negative electrode. The problems of dendrite growth are improved, the side reactions between the metal lithium and the electrolyte are reduced, the volume expansion is alleviated, the mechanical strength of the material is improved, the electrochemical performance of the battery is improved, especially the rate performance and the cycle life are improved, the capacity decay problem is improved, and the safety is improved.
[0026] The preparation method of the stable composite lithium metal negative electrode material of the present disclosure comprises: immersing the copper foil into the soaking solution, and performing a hydrothermal reaction to obtain a three-dimensional copper foil with a three-dimensional copper oxide structure; immersing the three-dimensional copper foil in an electroplating solution to perform electroplating to deposit an electroplated lithium layer on the surface of the three-dimensional copper foil, thereby obtaining a pre-prepared negative electrode material; immersing the pre-prepared negative electrode material in an artificial SEI infiltration solution to form an SEI protective layer on the surface of the electroplated lithium layer.
[0027] The preparation method of the present disclosure first generates a dense copper oxide three-dimensional surface on the surface of the copper foil through a hydrothermal reaction. The micron-level interconnected porous structure and high surface area of the self-grown nanosheet-shaped copper oxide three-dimensional structure can reduce the nucleation resistance of lithium, increase the nucleation sites, and reduce the polarization voltage, so that the ion and electron migration is less limited, ensuring uniform lithium nucleation and continuous smooth lithium plating layer in the subsequent process, and comprehensively improving the electrochemical stability of the composite lithium metal negative electrode. That is, by constructing a three-dimensional porous copper current collector, not only can the local current density be reduced to inhibit lithium dendrite growth, but also the deposited lithium can be accommodated to alleviate the volume change. In addition, as a lithiumophilic material, the lithiumophilic surface of the copper oxide material can contribute part of the capacity during the cycling process and exhibit excellent cycling stability in the subsequent cycling process.
[0028] After electroplating the metal lithium on the three-dimensional copper foil, the SEI protective layer is generated on the surface of the electroplated lithium layer by the infiltration method. This not only can satisfy the long-term storage of the negative electrode material in an oxygen-containing environment, reduce the preparation cost caused by the production environment requirements, but also can optimize the ion transmission path, reduce the generation of lithium dendrites, improve the electrochemical performance, especially the rate performance and the cycle life, and improve the safety of the battery prepared by the negative electrode material prepared by the preparation method.
[0029] The electroplating of the lithium layer on the three-dimensional copper foil to prepare the negative electrode material can reduce the amount of metal lithium compared to directly using lithium metal as the negative electrode, which is conducive to improving the utilization rate of lithium metal and reducing the cost.
[0030] Optionally, the soaking solution comprises a strong base, a halogenated metal salt, a persulfate salt, and a sulfate salt; wherein the strong base comprises at least one of sodium hydroxide, potassium hydroxide, magnesium hydroxide, calcium hydroxide, etc.; the halogenated metal salt comprises at least one of sodium chloride, potassium chloride, magnesium chloride, calcium chloride, zinc chloride, iron chloride, copper chloride, etc.; the persulfate salt comprises at least one of sodium persulfate, potassium persulfate, etc.; and the sulfate salt comprises at least one of sodium sulfate, potassium sulfate, magnesium sulfate, zinc sulfate, iron sulfate, and copper sulfate.
[0031] Optionally, the preparation method of the soaking solution comprises dissolving 10-200 mM of a strong base (for example, 10 mM, 30 mM, 50 mM, 70 mM, 100 mM, 120 mM, 150 mM, 180 mM, 200 mM, etc., which are not limited herein), 10-100 mM of a halogenated metal salt (for example, 10 mM, 20 mM, 30 mM, 40 mM, 50 mM, 60 mM, 70 mM, 80 mM, 90 mM, 100 mM, etc., which are not limited herein), 1-20 mM of a persulfate salt (for example, 1 mM, 2 mM, 5 mM, 7 mM, 10 mM, 12 mM, 15 mM, 18 mM, 20 mM, etc., which are not limited herein), and 0.01-1.0 mM of a sulfate salt (for example, 0.01 mM, 0.05 mM, 0.1 mM, 0.2 mM, 0.3 mM, 0.4 mM, 0.5 mM, 0.6 mM, 0.7 mM, 0.8 mM, 0.9 mM, 1.0 mM, etc., which are not limited herein) in 100 mL of water, and stirring uniformly, and heating to 60-90°C (for example, 60°C, 70°C, 80°C, 90°C, etc., which are not limited herein).
[0032] It should be noted that the present disclosure adopts a chemical in-situ growth method to form a CuO surface with lithium affinity on a copper foil, and the copper oxide three-dimensional structure layer is black and dense. The hydrothermal reaction time can be selected as required, as long as the black and dense copper oxide three-dimensional structure layer is grown on the copper foil.
[0033] Optionally, the hydrothermal reaction temperature is 60-90°C, for example, 60°C, 70°C, 80°C, 90°C, etc., which are not limited herein. A too high hydrothermal reaction temperature can cause the components (for example, the persulfate salt) in the soaking solution to decompose rapidly, so that only part of the raw materials in the soaking solution participate in the reaction, and it is difficult to reliably form the copper oxide three-dimensional structure. A too low hydrothermal reaction temperature can reduce the reaction activity, so that only part of the raw materials in the soaking solution participate in the reaction, and it is difficult to form a dense and uniform copper oxide three-dimensional structure surface.
[0034] Optionally, when growing the copper oxide three-dimensional structure on the surface of the copper foil by the hydrothermal reaction, the continuous liquid-replacement and liquid-supplement device can be used to hold the soaking liquid, and the copper foil can be placed in the device to perform the hydrothermal reaction. In this way, the concentration stability of the persulfate (e.g., potassium persulfate) in the soaking liquid can be ensured.
[0035] The continuous liquid-replacement and liquid-supplement device can refer to a device capable of continuously discharging the reacted soaking liquid and continuously supplementing new soaking liquid during the hydrothermal reaction.
[0036] Optionally, in order to maintain the stable progress of the hydrothermal reaction, the temperature of the new soaking liquid supplemented during the liquid-replacement and liquid-supplement can be preheated to the temperature of the hydrothermal reaction (i.e., 60-90°C).
[0037] Optionally, when generating the copper oxide three-dimensional structure, the density of the copper oxide three-dimensional structure can be detected online by the X-ray transmission technology, and the thickness and / or uniformity of the copper oxide three-dimensional structure can be detected online by the visual CCD detection technology, so as to ensure the uniformity of the three-dimensional copper foil (the good product appears uniform black, and the defective product has the original copper brown color of the copper foil).
[0038] For example, the thickness detection can be performed by taking a photo of the copper foil, and then analyzing the photo to generate the thickness of the copper oxide three-dimensional structure.
[0039] The direction of the online detection of the density or uniformity is similar to the related art, and will not be described here.
[0040] Optionally, before the hydrothermal reaction, the copper foil can be cleaned. For example, the copper foil can be sequentially cleaned by oxalic acid solution, deionized water, acetone solution, deionized water, and ethanol, and then dried before the hydrothermal reaction.
[0041] Optionally, after the generation of the copper oxide three-dimensional structure, the copper oxide three-dimensional structure can be cleaned by deionized water, and then dried.
[0042] Optionally, the hydrothermal reaction, the cleaning of the copper foil, and the cleaning and drying of the copper oxide three-dimensional structure after the generation of the copper oxide three-dimensional structure can be performed in an air atmosphere.
[0043] Optionally, the electroplating solution comprises a lithium salt, a solvent, and an additive; wherein the lithium salt comprises at least one of LiTFSI, LiPF6, Li2S6, LiNO3, LiFSI, the concentration of any one of LiTFSI, LiPF6, Li2S6, LiNO3, LiFSI is 0.2-2.0 mol / L (for example: 0.2 mol / L, 0.5 mol / L, 0.7 mol / L, 1.0 mol / L, 1.2 mol / L, 1.5 mol / L, 1.7 mol / L, 2.0 mol / L, etc., which are not specifically limited here); the solvent comprises at least one of DME, DOL, DMC, EC, PC, EMC, DUGLYME, FEC, MTFA, MP; the additive comprises but is not limited to nitrate and the like, for example: one or more of lithium nitrate (LiNO3), lithium nitrite (LiNO2), potassium nitrate (KNO3), cesium nitrate (CsNO3), magnesium nitrate (Mg(NO3)2), barium nitrate (Ba(NO3)2), potassium nitrite (KNO2), and cesium nitrite (CsNO2), the mass percentage concentration of any one of LiNO3, LiNO2, KNO3, CsNO3, Mg(NO3)2, Ba(NO3)2, KNO2, and CsNO2 is 0.5-3.0% (for example: 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, etc., which are not specifically limited here).
[0044] Optionally, after electroplating, washing and drying can be performed, and a smooth lithium layer surface can be obtained through a rolling process.
[0045] It should be noted that, due to the activity of lithium metal, electroplating, washing, drying, and rolling can be performed in an inert atmosphere; wherein electroplating, drying, and rolling can be further performed in a water-free environment.
[0046] Optionally, the current density of electroplating is 1-50 mA / cm 2 , for example: 1 mA / cm 2 , 5 mA / cm 2 , 10 mA / cm 2 , 15 mA / cm 2 , 20 mA / cm 2 , 25 mA / cm 2 , 30 mA / cm 2 , 35 mA / cm 2 , 40 mA / cm 2 , 45 mA / cm 2 , 50 mA / cm 2 , etc., which are not specifically limited here. The maximum current density that the three-dimensional copper foil can withstand is 50 mA / cm 2Further increasing the current density will result in the destruction of the three-dimensional copper oxide structure, and thus reduce the electrical performance of the negative electrode material.
[0047] Optionally, the plating capacity is 0.1-10 mAh / cm 2 , for example, 0.1 mAh / cm 2 , 0.5 mAh / cm 2 , 1 mAh / cm 2 , 3 mAh / cm 2 , 5 mAh / cm 2 , 8 mAh / cm 2 , 10 mAh / cm 2 , etc., which are not specifically limited herein.
[0048] Optionally, the plating time is 1-45 min, for example, 1 min, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, which are not specifically limited herein.
[0049] The plating deposition of lithium can be dynamic continuous plating, that is, the three-dimensional copper foil to be plated can be arranged on a conveying roller to move the three-dimensional copper foil to a plating station for plating by the conveying roller, and then conveyed to the next station for the next process after plating. During plating, the speed of the three-dimensional copper foil conveyed by the conveying roller, the current density, etc. can be adjusted according to the plating time.
[0050] During plating, the three-dimensional copper foil is connected to the plating negative electrode, and the lithium metal is connected to the plating positive electrode. During plating, the distance between the three-dimensional copper foil and the lithium metal connected to the positive electrode can be adjusted according to the thickness requirements of plating to achieve uniform deposition of lithium metal and achieve the target deposition thickness.
[0051] Optionally, the plating current density is 10-40 mA / cm 2 , for example, 10 mA / cm 2 , 15 mA / cm 2 , 20 mA / cm 2 , 25 mA / cm 2 , 30 mA / cm 2 , 35 mA / cm 2 , 40 mA / cm 2 , etc., which are not specifically limited herein. Plating under the condition of a relatively optimal current density can ensure the stability of the lithium plating layer to ensure that the prepared negative electrode material has good cyclic charge and discharge capacity.
[0052] Optionally, the plating capacity is 1-3 mAh / cm 2 , for example, 1 mAh / cm 2 , 1.5 mAh / cm2 2 mAh / cm2 2 2.5 mAh / cm2 2 3 mAh / cm2 2 etc., which are not specifically limited herein. If the plating capacity is too low, it cannot supply enough lithium ions to participate in the reaction; if the plating capacity is too high, it will cause the adhesion to decrease, resulting in the generation of lithium dendrites in advance.
[0053] Optionally, the plating time is 3-15 min, for example: 3 min, 5 min, 10 min, 15 min, which are not specifically limited herein. If the plating time is too short, it cannot supply enough lithium ions to participate in the reaction; if the plating time is too long, it will cause the adhesion to decrease, resulting in the generation of lithium dendrites in advance.
[0054] Optionally, cleaning can be performed after plating, and drying can be performed after rolling.
[0055] Optionally, the artificial SEI infiltrating solution includes a metal salt and an organic solvent; wherein the metal salt includes silver trifluoromethyl sulfonate (L-CAgF3O3S) with a concentration of 5.0-200.0 mmol / L (for example: 5.0 mmol / L, 10 mmol / L, 30 mmol / L, 50 mmol / L, 70 mmol / L, 100 mmol / L, 120 mmol / L, 150 mmol / L, 180 mmol / L, 200 mmol / L, etc., which are not specifically limited herein); the organic solvent includes at least one of N-methyl pyrrolidone, dimethyl sulfoxide, tetrahydrofuran, ethylene glycol dimethyl ether, and N,N-dimethylformamide.
[0056] The mechanism of preparing the SEI protective layer by infiltrating the artificial SEI infiltrating solution is as follows:
[0057]
[0058] According to the above mechanism, the artificial SEI protective layer prepared on the surface of the prefabricated anode material is constructed by the components in the artificial SEI infiltrating solution and Li to form a replacement, and a uniform hybrid mixed SEI layer composed of inorganic LiF, AgLi alloy, and -C-O- polymer is constructed; wherein the LiF component can control the horizontal growth of Li and avoid vertical deposition, because its surface energy is high, it can effectively inhibit the generation of lithium dendrites; the introduced Li-Ag alloy can compensate for the electronic insulation and low ionic conductivity of LiF, and the organic component can inhibit the volume expansion of lithium metal and tightly contact with the electrode.
[0059] Of course, in other embodiments, the metal salt can also include lithium salts and other metal salts, such as at least one of LiF, Li2CO3, LiOH, Li2O, LiCl, ROCO2Li, ROSO2Li (wherein the concentration of any one of LiF, Li2CO3, LiOH, Li2O, LiCl, ROCO2Li, ROSO2Li is 5.0-200.0 mmol / L), or at least one of LiPON, AlPO4.
[0060] It should be noted that the metal salt can include silver trifluoromethanesulfonate, and the above lithium salt and / or other metal salt, or only silver trifluoromethanesulfonate, or lithium salt or other metal salt.
[0061] In other embodiments, the artificial SEI infiltrating liquid can also include metal oxides, fluorides, film formers, cross-linking agents, etc.; wherein the metal oxides include but are not limited to at least one of Al2O3, SiO2, the fluorides include but are not limited to at least one of AlF3, LiF, the film formers include but are not limited to at least one of polyethylene oxide, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinyl alcohol, and the cross-linking agents include but are not limited to at least one of silicon tetrachloride, zinc chloride, lithium aluminum tetrahydride, lithium borohydride, sodium borohydride.
[0062] Optionally, the pre-prepared negative electrode material is infiltrated with the artificial SEI infiltrating liquid at a temperature of 10-80°C (for example: 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, etc., which are not specifically limited here).
[0063] Optionally, the time for infiltrating the pre-prepared negative electrode material with the artificial SEI infiltrating liquid is 1-600s, for example: 1s, 10s, 50s, 100s, 150s, 200s, 250s, 300s, 350s, 400s, 450s, 500s, 550s, 600s, etc., which are not specifically limited here.
[0064] Optionally, after the infiltration is completed, it can be dried and rolled, and then wound.
[0065] The application is further described in detail below in conjunction with examples.
[0066] Example 1 1. Take 75mM NaOH, 25mM NaCl, 10mM K2S2O8, 0.2mM CuSO4·5H2O raw materials according to the following standards, dissolve them in 100 mL of deionized water, stir uniformly, and heat to 70 ℃ to prepare a soaking liquid.
[0067] The surface dust-free clean copper foil with a thickness of 8 μm is placed in the prepared soaking solution (70°C), soaked until the copper foil surface presents a uniform black color, taken out, washed with deionized water 3 times, and placed in a 70°C oven for drying to prepare a three-dimensional copper foil with a three-dimensional copper oxide structure.
[0068] 2. The three-dimensional copper foil is cut into a circular piece with a diameter of 16 mm, lithium is used as the counter electrode in an inert atmosphere glove box, LiFSI (lithium bisfluorosulfonylimide) is dissolved in a mixed organic solvent of DME (dimethoxyethane, analytical pure) and DOL (1,3-dioxolane, analytical pure) in a volume ratio of 1:1 according to a concentration standard of 1 mol / L, and LiNO3 is additionally added based on the above mixed solution to obtain a mass percentage concentration of 1% to obtain an electroplating solution for lithium deposition, the current density is 32 mA / cm 2 , the electroplating time is 5 min, and after 100 kg planar pressing, the electroplating capacity is about 2.7 mAh / cm 2 , and a lithium metal negative electrode sheet with a three-dimensional copper foil current collector.
[0069] 3. The lithium metal negative electrode sheet with a three-dimensional copper foil current collector is soaked in an artificial SEI soaking solution (THF is used as the solvent, a 100 mM L-CAgF3O3S solution is prepared, and the temperature is 50°C) for 60 seconds, washed with the solvent (THF) used in the soaking solution, and naturally dried in an inert atmosphere to obtain a lithium metal negative electrode sheet with a three-dimensional copper foil current collector with an artificial SEI surface.
[0070] Example 2 1. 75 mM KOH, 25 mM NaCl, 10 mM K2S2O8, and 0.2 mM Na2SO4 raw materials are dissolved in 100 mL of deionized water according to the following standard, stirred uniformly, heated to 90°C, and a soaking solution is prepared.
[0071] The surface dust-free clean copper foil with a thickness of 8 μm is placed in the prepared soaking solution (90°C), soaked until the copper foil surface presents a uniform black color, taken out, washed with deionized water 3 times, and placed in a 70°C oven for drying to prepare a three-dimensional copper foil with a three-dimensional copper oxide structure.
[0072] 2. Cut the three-dimensional copper foil into a disc with a diameter of 16 mm, use lithium sheet as the counter electrode in a glove box filled with inert atmosphere, dissolve LiFSI (lithium bisfluorosulfonylimide) in organic solvent mixed with DME (dimethoxyethane, analytical pure) and DOL (1,3-dioxolane, analytical pure) at a volume ratio of 2:1 according to the concentration standard of 1 mol / L, and additionally add LiNO3 to the above mixed solution to make the mass percentage concentration of LiNO3 2%, to obtain an electroplating solution for lithium deposition by electroplating, the current density is 40 mA / cm 2 , the electroplating time is 4 min, and the electroplated capacity is about 2.7 mAh / cm 2 after 200 kg planar pressing, to obtain a lithium metal negative electrode sheet with a three-dimensional copper foil current collector.
[0073] 3. Soak the lithium metal negative electrode sheet with a three-dimensional copper foil current collector in an artificial SEI soaking solution (using a mixture of dimethoxyethane and tetrahydrofuran at a volume ratio of 1:1 as the solvent, and configuring the molar concentration of L -1 CAgF3O3S to be 125 mM, and the solution temperature is 25°C) for 30 seconds, wash with the solvent (THF) used in the soaking solution, and then naturally dry in an inert atmosphere to obtain a lithium metal negative electrode sheet with a three-dimensional copper foil current collector and an artificial SEI surface.
[0074] Example 3 1. Take 100 mM NaOH, 25 mM KCl, 5 mM Na2S2O8, and 0.1 mM MgSO4 raw materials dissolved in 100 mL of deionized water according to the following standard, stir uniformly, and heat to 60°C to prepare a soaking solution.
[0075] Put the surface dust-free clean copper foil with a thickness of 8 μm into the prepared soaking solution (60°C), soak until the copper foil surface presents a uniform black color, take out, wash with deionized water for 3 times, and put into a 70°C oven for drying to prepare a three-dimensional copper foil with a three-dimensional copper oxide structure.
[0076] 2. Cut the three-dimensional copper foil into a disc with a diameter of 16 mm, use lithium sheet as the counter electrode in a glove box filled with inert atmosphere, dissolve LiFSI (lithium bisfluorosulfonylimide) in organic solvent mixed with DME (dimethoxyethane, analytical pure) and DOL (1,3-dioxolane, analytical pure) at a volume ratio of 1:2 according to the concentration standard of 1 mol / L, and additionally add LiNO3 to the above mixed solution to make the mass percentage concentration of LiNO3 1%, to obtain an electroplating solution for lithium deposition by electroplating, the current density is 16 mA / cm 2 , the electroplating time is 4 min, and the electroplated capacity is about 1 mAh / cm 2A lithium metal negative electrode sheet with a three-dimensional copper foil current collector.
[0077] 3. The lithium metal negative electrode sheet with a three-dimensional copper foil current collector is soaked in an artificial SEI soaking solution (L-CaF3O3S solution with a molar concentration of 10 mM L -1 CAgF3O3S solution, solution temperature 25℃) for 10 seconds, washed with the solvent used for the soaking solution (tetrahydrofuran), and naturally dried in an inert atmosphere to obtain a lithium metal negative electrode sheet with a three-dimensional copper foil current collector with an artificial SEI surface.
[0078] Example 4 Example 4 differs from Example 1 in the soaking solution prepared in Step 1, Step 2, and the artificial SEI soaking solution and soaking temperature used in Step 3.
[0079] The preparation method of the soaking solution in Step 1 of Example 4 is as follows: Take 10 mM KOH, 10 mM MgCl2, 1 mM Na2S2O8, and 0.01 mM Na2SO4 raw materials dissolved in 100 mL of deionized water according to the following standards, stir uniformly, and heat to 60℃.
[0080] Step 2 of Example 4 is as follows: Cut the three-dimensional copper foil into a circular sheet with a diameter of 16 mm, use lithium sheet as the counter electrode in an inert atmosphere glove box, dissolve LiFSI in a mixed organic solvent of DME (glycol dimethyl ether, analytical pure) and DOL (1,3-dioxolane, analytical pure) with a volume ratio of 1:1 according to the concentration standard of 0.2 mol / L, and additionally add LiNO2 based on the above mixed solution to make the mass percentage concentration of LiNO2 0.5%, to obtain an electroplating solution for lithium deposition by electroplating, current density 16 mA / cm 2 , electroplating time 4 min, and after 200 kg planar pressing, the electroplating capacity is about 1 mAh / cm 2 , a lithium metal negative electrode sheet with a three-dimensional copper foil current collector.
[0081] The artificial SEI soaking solution and soaking temperature in Step 3 of Example 4 are as follows: Soaking solution: L-CaF3O3S solution with a molar concentration of 200 mM, using tetrahydrofuran THF as the solvent; soaking temperature: 10℃.
[0082] Example 5 Example 5 differs from Example 1 in the soaking solution prepared in Step 1, Step 2, and the artificial SEI soaking solution and soaking temperature used in Step 3.
[0083] The preparation method of the soaking solution in step 1 of Example 5 is as follows: Take 200 mM calcium hydroxide, 100 mM calcium chloride, 20 mM Na2S2O8, 1.0 mM zinc sulfate raw material solution in 100 mL of deionized water according to the following standard, stir uniformly, heat to 90 ℃.
[0084] Step 2 of Example 5 is as follows: Cut the three-dimensional copper foil into a circular sheet with a diameter of 16 mm, and use lithium sheet as the counter electrode in the glove box filled with inert atmosphere. Dissolve LiPF6 in the organic solvent mixed with DME (glycol dimethyl ether, analytical pure) and DOL (1,3-dioxolane, analytical pure) at a volume ratio of 1:1 according to the concentration standard of 2.0 mol / L, and additionally add CsNO2 based on the above mixed solution to obtain an electroplating solution with a mass percentage concentration of CsNO2 of 3.0% for lithium deposition by electroplating. The current density is 16 mA / cm 2 , the electroplating time is 4 min, and the electroplating capacity of the three-dimensional copper foil current collector with three-dimensional structure is about 1 mAh / cm 2 after 200 kg planar pressing.
[0085] The artificial SEI infiltration solution and infiltration temperature of step 3 of Example 5 are as follows: Infiltration solution: L-CAgF3O3S solution with a molar concentration of 5.0 mM is prepared using tetrahydrofuran (THF) as the solvent; Infiltration temperature: 80℃.
[0086] Test Example 1 Take 75 mM NaOH, 25 mM NaCl, 10 mM K2S2O8, 0.2 mM CuSO4·5H2O raw material solution in 100 mL of deionized water according to the following standard, stir uniformly, heat to 70 ℃, and prepare the soaking solution.
[0087] Put the surface dust-free clean copper foil with a thickness of 8 μm into the prepared soaking solution (80℃), soak until the copper foil surface presents uniform black color, take out, wash with deionized water for 3 times, and dry in a 70℃ oven to prepare a three-dimensional copper foil with three-dimensional copper oxide structure.
[0088] Scan the three-dimensional copper foil with three-dimensional copper oxide structure under high magnification electron microscope and low magnification electron microscope respectively, and the results are as follows: Figure 1 and Figure 2 .
[0089] Assemble a coin cell battery with the three-dimensional copper foil with three-dimensional copper oxide structure as the positive electrode (working electrode) and lithium sheet as the negative electrode, and perform electrochemical performance test: First, the battery is cycled at a small current of 50 μA between 0-1 V (vs. Li + / Li) for 10 times to complete the activation step to remove impurities and pre-form SEI film; the discharge is to deposit lithium on the current collector.
[0090] Discharge at a constant current density of 1.0 mA / cm 2 , charge to 0.5 V cutoff to calculate the coulombic efficiency of lithium deposition / dissolution. In each cycle, the time of lithium deposition process is set to 1 h, and the cutoff voltage of lithium dissolution process is 1.0 V. The lithium deposition / dissolution coulombic efficiency is plotted against the cycle number, and the voltage vs. capacity plot can obtain the potential difference of deposition / dissolution and the nucleation overpotential, the results are shown in Figure 3 and Figure 4 .
[0091] Test Example 2 The battery is prepared by using bare copper foil (i.e., copper foil without copper oxide three-dimensional structure) and tested by the method of Test Example 1, and the test results are shown in Figure 3 and Figure 5 .
[0092] According to Figure 3 , Figure 4 and Figure 5 , it can be seen that Test Example 1 can comprehensively improve the electrochemical stability of the battery by growing copper oxide three-dimensional structure in situ on the copper foil.
[0093] Among them, Test Example 1 constructs three-dimensional copper foil by hydrothermal reaction, realizes the improvement of battery coulombic efficiency (about 20% + ), and reduces the material polarization voltage (reduces 35%+); the smaller the voltage polarization, the less the ion and electron migration is limited, which is beneficial to ensure uniform Li nucleation and continuous smooth Li plating layer. At the same time, the micron-level interconnected porous structure and its high surface area can reduce the Li nucleation resistance, increase the nucleation site, and promote the uniform deposition of lithium ions; the increase of the thickness of the pore layer, the increase of the specific surface area and the pore volume can also effectively alleviate the volume effect in the charging and discharging process, and further improve the electrochemical performance of the battery.
[0094] Test Example 3 The difference between Test Example 3 and Test Example 1 is that the temperature for growing copper oxide three-dimensional structure in situ by hydrothermal reaction is 95°C. Other processes, and the method of preparing a battery for testing, all refer to Test Example 1.
[0095] The three-dimensional copper foil with copper oxide three-dimensional structure is scanned under high-power electron microscope and low-power electron microscope, respectively, and the results are shown in Figure 6 and Figure 7 .
[0096] Test Example 4 The difference between Test Example 4 and Test Example 1 is that the temperature for in-situ growth of copper oxide three-dimensional structure in the hydrothermal reaction is 55°C. Other processes, and the method for preparing into a battery for testing, are all referred to Test Example 1.
[0097] Scanning the three-dimensional copper foil with copper oxide three-dimensional structure under high-magnification electron microscope and low-magnification electron microscope respectively, the results will be Figure 8 and Figure 9 .
[0098] According to Figure 1 , Figure 2 , Figure 6 , Figure 7 , Figure 8 and Figure 9 , it is known that if the temperature of the hydrothermal reaction is too high (greater than 90°C), the sulfate is rapidly decomposed, only part of the reaction on the surface of the material is involved, not only the reaction process cannot be accelerated, but also the effect of generating copper oxide three-dimensional structure is poor; if the temperature of the hydrothermal reaction is too low (less than 60°C), the reaction activity is reduced, only a small part of the reaction on the surface of the material is involved, and a dense and uniform copper oxide three-dimensional structure surface cannot be formed.
[0099] Test Example 5 Assembling a button cell with the lithium metal negative electrode sheet with three-dimensional structure copper foil current collector of Example 1; wherein the positive electrode is lithium iron phosphate / NCM811 sheet.
[0100] Battery preparation: the opening surface of the positive electrode shell is upward, and is placed horizontally on the operation table; the sheet and the gasket are placed into the negative electrode shell with tweezers, and the lithium metal negative electrode sheet with three-dimensional structure copper foil current collector is placed in the middle of the negative electrode shell; a plastic dropper is used to take 1 mol / L LiPF6 (lithium hexafluorophosphate) solution in EC (ethylene carbonate) and EMC (methyl ethyl carbonate) 3:7 volume ratio mixed organic solvent, and additional 10% mass concentration FEC electrolyte is added to soak the surface; the separator is clamped to evenly cover the negative electrode sheet; the electrolyte is dripped again to wet the surface of the separator; the positive electrode sheet is clamped and placed in the middle of the separator; the gasket is clamped and placed on the positive electrode, and is strictly aligned; the positive electrode shell is clamped with tweezers to cover it; and a button cell sealing machine is used for sealing.
[0101] Testing the rate performance of the battery of Test Example 5: The rate performance of the battery of Test Example 5 is tested under the constant current density of 0.2C / 0.5C / 1C / 2C / 5C (LFP: 1C=170 mAh / g; NCM: 1C=200 mAh / g), and the current density is gradually decreased to 0.2C in turn. The charge and discharge capacity is plotted with the cycle number, and the cycle rate capacity curve is obtained, and the results are shown in Figure 10 andFigure 11 .
[0102] Test Example 6 Test Example 6 differs from Test Example 5 in that a lithium layer is electroplated on a bare copper foil (i.e., a copper foil without a three-dimensional copper oxide structure) when preparing the negative electrode.
[0103] The negative electrode material is prepared into a battery in the manner of Test Example 5, and tested, with the results shown in Figure 10 and Figure 11 .
[0104] Test Example 7 Test Example 7 differs from Test Example 5 in that pure lithium metal is used as the negative electrode sheet.
[0105] The negative electrode material is prepared into a battery in the manner of Test Example 5, and tested, with the results shown in Figure 10 and Figure 11 .
[0106] According to Figure 10 and Figure 11 , the three-dimensional copper foil constructed by the hydrothermal reaction exhibits excellent rate performance after electroplating of lithium. Among them, compared with a bare copper foil, the lithium-philic CuO three-dimensional copper foil can effectively improve the cycle stability of the material, and the stability is better at a low rate; compared with a pure lithium negative electrode, the electroplated lithium deposition can achieve better cycle performance within 10% of the lithium metal used, and the reduction of lithium metal not only reduces the cost but also improves the safety performance of the battery using lithium as the negative electrode.
[0107] Test Example 8 Test Example 8 differs from Test Example 5 in that the current density for electroplating to prepare the lithium layer is 64 mA / cm 2 .
[0108] The negative electrode material of Test Example 8 is prepared into a battery in the manner of Test Example 5, and tested, with the results shown in Figure 12 .
[0109] Test Example 9 Test Example 9 includes Test Example 9-1 and Test Example 9-2.
[0110] Test Example 9-1 differs from Test Example 5 in that the current density for electroplating to prepare the lithium layer is 16 mA / cm 2 .
[0111] Test Example 9-2 differs from Test Example 5 in that the current density for electroplating to prepare the lithium layer is 32 mA / cm 2 .
[0112] The negative electrode material of Test Example 9 is prepared into a battery in the manner of Test Example 5, and tested, with the results shown in Figure 12 .
[0113] According to Figure 12 It can be seen that with the increase of the plating current density, the stability of the Li plating layer decreases. The 1 C cycle capacity of the lithium metal negative electrode prepared by plating on the three-dimensional copper foil at current densities of 16 / 32 / 64 mA / cm 2 is 101 / 118 / 35 mAh / g respectively after 100 cycles. It can be seen that when the current density is less than 60 mA / cm 2 , the electrical performance can be improved.
[0114] Test Example 10 The lithium metal negative electrode sheet with artificial SEI surface prepared in Example 1 was used to assemble a button cell; wherein the positive electrode was a lithium iron phosphate / NCM811 electrode sheet.
[0115] Battery preparation: the opening surface of the positive electrode shell was upward, and was placed flat on the operation table; the negative electrode shell was placed into the positive electrode shell with tweezers, and the lithium metal negative electrode sheet with artificial SEI surface was placed in the middle of the negative electrode shell; a plastic dropper was used to take 1 mol / L LiPF6 (lithium hexafluorophosphate) in EC (ethylene carbonate) and EMC (ethyl carbonate) mixed organic solvent with a volume ratio of 3:7, and additional 10% FEC by mass fraction, and the electrolyte was used to soak the surface; the separator was clamped and evenly covered on the negative electrode sheet; the electrolyte was dripped again to wet the surface of the separator; the positive electrode sheet was clamped and placed in the middle of the separator; the gasket was clamped and placed on the positive electrode, and was strictly aligned; the positive electrode shell was clamped with tweezers to cover it; and a button cell sealing machine was used for sealing.
[0116] The battery of Test Example 10 was tested in the manner of Test Example 5, and the results are shown in Figure 13 .
[0117] The cycle stability was tested at a constant 1 C rate, and the results are shown in Figure 14 .
[0118] Test Example 11 The difference between Test Example 11 and Test Example 10 is that when preparing the negative electrode, a lithium layer is plated on the bare copper foil (i.e. copper foil without copper oxide three-dimensional structure), and then soaked in the artificial SEI soaking solution.
[0119] The negative electrode material was made into a battery in the manner of Test Example 10, and was tested, and the results are shown in Figure 13 and Figure 14 .
[0120] According to Figure 13 and Figure 14 , the lithium metal negative electrode sheet with artificial SEI surface prepared in Example 1 is used to prepare a composite negative electrode material based on three-dimensional copper foil, which has better cycle stability under high rate working conditions compared to different copper foils.
[0121] Experimental Example 12 XRD tests were performed on the lithium metal anode sheet with an artificial SEI surface from Example 1. The results are shown in [Figure 1]. Figure 15 .
[0122] according to Figure 15 It is known that the successful polymerization of oligomers on the surface of lithium metal anode plates with artificial SEI surfaces and the successful formation of inorganic components can utilize the artificially formed SEI protective layer to optimize ion transport paths, reduce the formation of lithium dendrites, and improve electrochemical performance, especially rate performance and cycle life.
[0123] Experimental Example 13 The lithium metal anode sheet with an artificial SEI surface from Example 1 and a lithium metal sheet were exposed to air, and the changes on both surfaces were observed. The results are shown in [Figure 1]. Figure 16 .
[0124] according to Figure 16 It can be seen that the lithium metal anode with added artificial SEI protective layer did not undergo significant changes when exposed to air, thus avoiding material damage and resource waste in air-exposed scenarios and providing a higher possibility for the large-scale mass production of lithium metal.
[0125] Test Example 14 In-situ XRD tests were performed on the lithium metal anode sheet with an artificial SEI surface from Example 1. The results are shown in [Figure 1]. Figure 17 .
[0126] according to Figure 17 It is evident that an Ag-Li layer forms on the lithium metal surface after artificial SEI wetting, which remains relatively stable during cycling without structural changes. This indicates that artificial SEI wetting can replace the Li on the three-dimensional copper foil with the components in the wetting solution, resulting in a uniformly hybridized SEI layer (composed of inorganic LiF, AgLi alloy, and a -CO- polymer). This allows for several advantages: firstly, the horizontal growth of Li can be controlled by the LiF component, preventing vertical deposition due to its high surface energy, which effectively suppresses lithium dendrite formation; secondly, the introduced Li-Ag alloy compensates for the electronic insulation and low ionic conductivity of LiF; and thirdly, the organic components can suppress the volume expansion of lithium metal and ensure close contact with the electrode.
[0127] Experimental Example 15 The lithium metal negative electrode tab with the three-dimensional copper foil current collector in Example 1 is soaked in artificial SEI soaking liquid (THF as solvent, 10 / 100 / 200 mM / L CAgF3O3S solution, temperature 50 DEG C) of different concentrations for 60 seconds, washed with the solvent (THF) used in the soaking liquid, and naturally dried in an inert atmosphere. The cross section of the tab treated by the solution of different concentrations is observed under an electron microscope, and the results are as follows Figure 18 Figure 18 The CAgF3O3S concentration in the artificial SEI soaking liquid from left to right is 10 mM / L, 100 mM / L and 200 mM / L, respectively. Among them, the 100 mM / L CAgF3O3S solution has the best soaking effect, and forms an Ag-Li artificial SEI layer with a certain thickness without excessive consumption of the lithium metal layer.
[0128] In summary, the negative electrode material prepared by the preparation method can be used to prepare a battery. The preparation method grows a lithiumophilic copper oxide coating layer on the surface of the copper foil current collector in situ, constructs a high-performance lithium metal layer through an electroplating process, and constructs an artificial SEI layer on the basis of the structure to finally form a sandwich structure lithium metal composite negative electrode, which can improve the problem of dendrite growth, reduce the side reaction between the metal lithium and the electrolyte, relieve the volume expansion, improve the electrochemical performance of the battery, especially the rate performance and the cycle life, improve the capacity decay problem, and improve the safety.
[0129] The above only describes the preferred embodiments of the present application and is not intended to limit the present application. For those skilled in the art, the present application can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a high-stability composite lithium metal anode material, characterized in that, The application relates to a preparation method of a high-stability composite lithium metal negative electrode material. The copper foil is immersed in a soaking solution, a hydrothermal reaction is carried out, and a three-dimensional copper foil with a three-dimensional copper oxide structure is prepared; The three-dimensional copper foil is placed in an electroplating solution to carry out electroplating, so that an electroplated lithium layer is deposited on the surface of the three-dimensional copper foil to obtain a prefabricated negative electrode material; The prefabricated negative electrode material is infiltrated with an artificial SEI infiltrating solution to form an SEI protective layer on the surface of the electroplated lithium layer.
2. The method of claim 1, wherein the high-stability composite lithium metal anode material is prepared by the steps of: (a) preparing a lithium metal layer; (b) preparing a solid electrolyte layer; (c) preparing a current collector layer; and (d) preparing a protective layer. The temperature of the hydrothermal reaction is 60-90 DEG C.
3. The method of claim 1, wherein the high-stability composite lithium metal anode material is prepared by the steps of: (a) preparing a lithium metal layer; (b) preparing a solid electrolyte layer on the lithium metal layer; and (c) preparing a current collector layer on the solid electrolyte layer. The current density of the electroplating is 1-50 mA / cm 2 ; and / or, The capacity of the electroplating is 0.1-10 mAh / cm 2 ; and / or, The electroplating time is 1-45 min.
4. The method of claim 1, wherein the high-stability composite lithium metal anode material is prepared by the steps of: The current density of the electroplating is 10-40 mA / cm 2 ; and / or, The capacity of the electroplating is 1-3 mAh / cm 2 ; and / or, The electroplating time is 3-15 min.
5. The method for preparing the high-stability composite lithium metal anode material according to claim 1, characterized in that, The prefabricated negative electrode material is infiltrated with the artificial SEI infiltrating solution with a temperature of 10-80 DEG C; and / or, The prefabricated negative electrode material is infiltrated with the artificial SEI infiltrating solution for 1-600 s.
6. The method of claim 1, wherein the high-stability composite lithium metal anode material is prepared by the steps of: (a) preparing a lithium metal layer; (b) preparing a solid electrolyte layer; and (c) preparing a current collector layer. The soaking solution comprises a strong alkali, a halogenated metal salt, a persulfate and a sulfate; wherein, The strong alkali comprises at least one of sodium hydroxide, potassium hydroxide, magnesium hydroxide and calcium hydroxide; The halogenated metal salt comprises at least one of sodium chloride, potassium chloride, magnesium chloride, calcium chloride, zinc chloride, iron chloride and copper chloride; The persulfate comprises at least one of sodium persulfate and potassium persulfate; The sulfate comprises at least one of sodium sulfate, potassium sulfate, magnesium sulfate, zinc sulfate, iron sulfate and copper sulfate.
7. The method for preparing the high-stability composite lithium metal anode material according to claim 6, characterized in that, The preparation method of the soaking solution comprises dissolving 10-200 mM of the strong alkali, 10-100 mM of the halogenated metal salt, 1-20 mM of the persulfate and 0.01-1.0 mM of the sulfate in 100 mL of water, stirring uniformly and heating to 60-90 DEG C.
8. The method of claim 1, wherein the high-stability composite lithium metal anode material is prepared by the steps of: (a) preparing a lithium metal layer; (b) preparing a solid electrolyte layer; (c) preparing a lithium metal oxide layer; and (d) preparing a lithium metal oxide layer. The electroplating solution comprises a lithium salt, a solvent and an additive; wherein, The lithium salt comprises at least one of LiTFSI, LiPF6, Li2S6, LiNO3 and LiFSI, and the concentration of any one of LiTFSI, LiPF6, Li2S6, LiNO3 and LiFSI is 0.2-2.0 mol / L; The solvent comprises at least one of DME, DOL, DMC, EC, PC, EMC, DUGLYME, FEC, MTFA and MP; The additive comprises at least one or more of LiNO3, LiNO2, KNO3, CsNO3, Mg (NO3) 2, Ba (NO3) 2, KNO2 and CsNO2, and the mass percentage concentration of any one of LiNO3, LiNO2, KNO3, CsNO3, Mg (NO3) 2, Ba (NO3) 2, KNO2 and CsNO2 is 0.5-3.0%; And / or, The artificial SEI infiltrating solution comprises a metal salt and an organic solvent; wherein, the metal salt comprises silver trifluoromethyl sulfonate with a concentration of 5.0-200.0 mmol / L; The organic solvent comprises at least one of N-methyl pyrrolidone, dimethyl sulfoxide, tetrahydrofuran, ethylene glycol dimethyl ether and N, N-dimethylformamide.
9. A high-stability composite lithium metal anode material, characterized in that, The battery is prepared from the high-stability composite lithium metal negative electrode material prepared by the preparation method of the high-stability composite lithium metal negative electrode material in any one of claims 1-8.
10. A battery, characterized by The battery is prepared from the high-stability composite lithium metal negative electrode material prepared by the preparation method of the high-stability composite lithium metal negative electrode material in any one of claims 1-8.